2011
DOI: 10.1007/s11250-011-9958-2
|View full text |Cite
|
Sign up to set email alerts
|

Viral nucleoprotein localization and lesions of Newcastle disease in tissues of indigenous ducks

Abstract: Localization of Newcastle disease viral nucleoprotein and pathological lesions was evaluated in tissues of 55 indigenous ducks (45 experimentally infected and 10 sentinel ones). In addition, ten Newcastle disease infected chickens were used to ensure that the virus inoculum administered to the ducks produced the disease in chickens, the susceptible hosts. Ducks were killed on day 1, 4, 8 and 14 post-infection. Post-mortem examination was done with six tissues (liver, spleen, lung, caecal tonsils, kidneys and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In general, the multisystemic distribution of NDV antigen was demonstrated by IHC staining and was abundant in the immune organs at 2 d.p.i. This showed that NDV could replicate during the early stage of infection, and the immunoassay demonstrated NDV antigens in macrophagelike mononuclear cells in areas infiltrated with many lymphocytic cells (Njagi et al, 2012). It is possible that these cells play a significant role in viral replication in geese.…”
Section: Discussionmentioning
confidence: 88%
“…In general, the multisystemic distribution of NDV antigen was demonstrated by IHC staining and was abundant in the immune organs at 2 d.p.i. This showed that NDV could replicate during the early stage of infection, and the immunoassay demonstrated NDV antigens in macrophagelike mononuclear cells in areas infiltrated with many lymphocytic cells (Njagi et al, 2012). It is possible that these cells play a significant role in viral replication in geese.…”
Section: Discussionmentioning
confidence: 88%